Liquidity Constraints and Credit Card Delinquency: Evidence from Raising Minimum Payments - d’Astous, Philippe; Shore, Stephen H. (Journal of Financial and Quantitative Analysis, 2017)
We use credit card data to estimate the impact of increasing minimum payments on delinquency, payments, spending, and write-offs. Our identification strategy exploits an unusual institutional feature: Borrowers can use their account to make purchases with both revolving loans (on which minimum payments increased) and term loans (on which there was no change). Payment increases by delinquent borrowers are insufficient to match increasing minimums, resulting in lower cure rates and an increase in write-offs. Affected borrowers migrate away from these accounts by decreasing charges and increasing payments, consequently lowering the interest earned by the bank.